Art, popular culture and the classical ideal in the 1930s two classic films : a study of Roman Scandals and Christopher Strong - Soren, David 1973- (Midnight Marquee Press, 2010)
David Soren examines 2 classic films of the 1930s, Roman Scandals and Christopher Strong, exploring their relationships to society at that time and their importance today. We see how these films were products of their times, the Depression, corruption in politics, radio as a powerful new medium, design becoming streamlined in everything from clothes to cars and buildings. One of the most important points of this book is that it contains the unfinished autobiography of one of the first female film directors, Dorothy Arzner. While Arzner did not continue her autobiography beyond her youth, Soren provides a history of her entry into Hollywood and covers her films in detail
"Includes the unfinished autobiography of Dorothy Arzner" --Cover
Keywords: Arzner, Dorothy / 1900-1979; Arzner, Dorothy -- 1900-1979; Roman scandals (Motion picture); Christopher Strong (Motion picture); Motion picture producers and directors / United States / Biography; Motion picture producers and directors; United States